Prognostic Factors of Developmental Outcome in Neonatal Seizures in Term Infants - Yin-Hsuan Lai; Che-Sheng Ho; Nan-Chang Chiu; Chih-Fan Tseng; Yuan-Ling Huang (Elsevier, 2013)
The purpose of this study was to identify prognostic indicators of neurodevelopmental outcome in term infants who experienced clinical neonatal seizure. Methods: This is a retrospective, observational hospital-based study. Term infants who experienced clinical neonatal seizure between January 1999 and December 2009 were enrolled. Adverse outcomes were defined as death, cerebral palsy, global developmental delay, and/or epilepsy. The associations between adverse outcomes and 17 variables, including sex, mode of delivery, being small of gestational age, maternal illness, perinatal insults, meconium stained liquor, Apgar score at 1 and 5 minutes, seizure onset age, seizure type, etiology, electroencephalography (EEG) findings, antiepileptic drug efficacy, presence of metabolic acidosis, and cranial ultrasonographic findings, and presence of congenital heart disease were analyzed. Results: Among the 232 enrolled infants, 125 had a normal outcome and 14 had mild functional disability (59.9%), and 55 (23.7%) survived with one or more neurodevelopmental impairments (7 with cerebral palsy, 48 with global developmental delay), and 38 (16.4%) died. Forty-seven (23.0%) of the 204 patients who survived after the first discharge had epilepsy. Ten variables were associated with adverse outcome on univariate analysis, but only four variables, i.e., including abnormal cranial ultrasonography findings, abnormal anterior cerebral artery resistance index, abnormal EEG findings, and presence of congenital heart disease were independent predictors on multivariate logistic regression analysis. Conclusion: In term infants with neonatal seizures, several risk factors related to adverse outcome were recognized. Physicians should pay more attention to these factors when handling patients with neonatal seizures.